Sustainability and diversity in the architecture of intercultural universities in Mexico - Peña Dalia; Mesquida Peri (Environmental Science and Sustainable Development, 2022)
Intercultural universities in Mexico have been created since 2001, currently there are 12, the last one to be created is the Intercultural University of Baja California in San Quintin. These universities are governed by an intercultural model that states that they must incorporate linguistic expressions and manifestations and knowledge of indigenous peoples in their substantive functions as well as in their scientific activity, but some of them have also incorporated cultural and sustainable expressions in their architecture. In this sense, there are experiences of these universities that incorporate different cultural and sustainable elements in their architecture. Based on the above, this study presents some experiences of Intercultural Universities in Mexico that recover cultural and sustainable elements in their architecture. Methodologically, we resorted to reflexive ethnography by conducting several interviews with the architect of the UICEH. Some of the results obtained in the research show the importance of how, through the architectural spaces, elements of interculturality and sustainability are embodied, including some related to local cultures where the Universities have an impact.